Diagnostic performance of state-of-the-art imaging techniques for morphological assessment of vascular abnormalities in patients with chronic thromboembolic pulmonary hypertension (CTEPH) - Ley, Sebastian; Ley-Zaporozhan, Julia (European radiology, 2012)
Objectives: To determine the most comprehensive imaging technique for the assessment of pulmonary arteries in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Methods: 24 patients with CTEPH were examined by ECG-gated multi-detector CT angiography (MD-CTA), contrast-enhanced MR angiography (ce-MRA) and selective digital subtraction angiography (DSA) within 3 days. Two readers in consensus separately evaluated each imaging technique (48 main, 144 lobar and 449 segmental arteries) for typical changes like complete obstructions, vessel cut-offs, intimal irregularities, incorporated thrombus formations, and bands and webs. A joint interpretation of all three techniques served as a reference standard. Results: Based on image quality, there was no non-diagnostic examination by either imaging technique. DSA did not sufficiently display 1 main, 3 lobar and 4 segmental arteries. The pulmonary trunk was not assessable by DSA. One patient showed thrombotic material at this level only by MD-CTA and MRA. Sensitivity and specificity of MD-CTA regarding CTEPH-related changes at the main/lobar and at the segmental levels were 100%/100% and 100%/99%, of ce-MRA 83.1%/98.6% and 87.7%/98.1%, and of DSA 65.7%/100% and 75.8%/100%, respectively. Conclusion: ECG-gated MD-CTA proved the most adequate technique for assessment of the pulmonary arteries in the diagnostic work-up of CTEPH patients.